2006
DOI: 10.1590/s0102-311x2006000200006
|View full text |Cite
|
Sign up to set email alerts
|

Hipertensão arterial em idosos: prevalência, fatores associados e práticas de controle no Município de Campinas, São Paulo, Brasil

Abstract: The objective of this study was to assess the prevalence of reported hypertension among the elderly in Campinas, São Paulo, Brazil, identifying related factors, the use of healthcare services, and knowledge and practices related to treatment options. This was a cross-sectional population-based study, with stratified clustered multiple-stage sampling. Data analysis for the 426 individuals (60 years of age and older) considered the sampling design and outlining effect. Hypertension prevalence was 51.8% (46.4% in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
26
2
117

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(160 citation statements)
references
References 13 publications
15
26
2
117
Order By: Relevance
“…This fact can be confirmed in accordance with the studies of (18,19), which found that in Brazil there is a higher prevalence of elderly women and that this difference increases within the aging process. This fact becomes evident and may be attributed to a greater tendency for self-care, less exposure to external agents of greater risk to health such as smoking, alcohol use, occupational factors and greater medical assistance (20), in his study, adds that the reason for the demand for Pilates is greater among women due to therapeutic and aesthetic problems.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This fact can be confirmed in accordance with the studies of (18,19), which found that in Brazil there is a higher prevalence of elderly women and that this difference increases within the aging process. This fact becomes evident and may be attributed to a greater tendency for self-care, less exposure to external agents of greater risk to health such as smoking, alcohol use, occupational factors and greater medical assistance (20), in his study, adds that the reason for the demand for Pilates is greater among women due to therapeutic and aesthetic problems.…”
Section: Discussionsupporting
confidence: 91%
“…In relation to the health conditions, in a study similar to ours, it was found that most of the elderly practitioners of the Pilates reported health problems (60%), being the most common pathology the systemic arterial hypertension/SAH, thus reinforcing our study in which such pathologies do not prevent the practice of the Pilates method (23). The study (19) pointed out that, hypertensive elderly patients recognized that with the inclusion of physical activity and diet in their daily life there was a positive result in the control of hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Dentre os principais problemas de saúde que informaram apresentar, os cinco primeiros (74,7%) referem-se a: "hipertensão arterial" (23,6%), "diabetes" (17,1%), "gripe" (13,8%), "reumatismo" (11,7%) e "diarreia" (8,5%). Quanto à hipertensão arterial e reumatismo, as proporções referidas foram menores que as encontradas em estudos que investigaram grupos semelhantes 25,26,27 , e em relação ao diabetes, o resultado encontrado é semelhante aos descritos por Lebrão e Laurenti 25 para a cidade de São Paulo.…”
Section: Resultsunclassified
“…Essa tendência de excesso de peso e risco já foi identificada em outros estudos com idosas [21][22][23] que mostram prevalências de obesidade aproximadas, e mesmo superiores, a 50%. Apesar disso, a inserção de idosos em programas de exercícios físicos parece contribuir para a manutenção do estado nutricional nas diferentes etapas do envelhecimento 24 .…”
Section: Discussionunclassified